Group decision making with multi-attribute crisp and interval data and its application to supplier selection problem. (2018) - Azadfallah, Mohammad
This paper extends the Visekriterijumska Optimizacija I Komprosno Resenje (VIKOR) and the technique for order preferences by similarity to an ideal solution (TOPSIS) method for solving multiple attribute group decision making (MAGDM) problems under crisp and interval data (particularly, VIKOR with crisp and interval data, and TOPSIS only with interval data). In continuation, three new entropy-based approaches are introduced to determine the importance of decision makers (DMs) in group decision-making process. In addition, to determine the weights of the attributes, conventional entropy method with both crisp and interval data was used. Then, by using the weights of DMs, all individual decisions are aggregated into a collective decision. Finally, three numerical examples in supplier selection context are given to illustrate the feasibility and practability of the proposed MAGDM methods. In order to show the validation of the models a comparative analysis is done by comparing the results of the individual and average of all individual decisions with the extended models. The results indicate that the accuracy of the decision has been increased by considering the DMs' weights.